2008
DOI: 10.1080/08860220802212973
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Cystatin C with C-Reactive Protein and Apolipoprotein A1 in Patients on Hemodialysis

Abstract: Cystatin C is considered an indicator of acute renal failure and also a risk factor of cardiovascular disease. This study was undertaken to examine the relationship of serum cystatin C with C-reactive protein (CRP), lipids, and lipid-related compounds in patients on hemodialysis (HD). Cystatin C, CRP, total cholesterol, triglycerides, HDL cholesterol, LDL cholesterol, and apolipoprotein A1 and B were analyzed in serum of 30 patients on HD for 118 ± 18 months with low-flux dialyzers, before and after HD. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…As mentioned earlier, cystatin C seems to be a related inflammatory process. A possible implication of cystatin C in the inflammatory process was seen by a significant correlation with CRP, apolipoprotein A1, and monocytes, which play an important role in chronic inflammation and atherosclerosis [47][48][49]. Ferraro and colleagues recently described that inflammatory cytokines mainly contribute to perturb the cystatin C-cathepsins equilibrium in pathological mechanisms promoting several diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, cystatin C seems to be a related inflammatory process. A possible implication of cystatin C in the inflammatory process was seen by a significant correlation with CRP, apolipoprotein A1, and monocytes, which play an important role in chronic inflammation and atherosclerosis [47][48][49]. Ferraro and colleagues recently described that inflammatory cytokines mainly contribute to perturb the cystatin C-cathepsins equilibrium in pathological mechanisms promoting several diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] The high level of PCT, on the other hand, has been linked to the effect of cytokines released due to the microvascular interaction during HD. These studies have reported that both of these parameters are higher than those in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported that both of these parameters are higher than those in the normal population. 2,[5][6][7][8][9][10][11][12][13][14][15][16] Studies have linked the high level of CRP to the fact that when leukocytes face the dialysis membranes, the cytokines released from inflammatory cells trigger the inflammatory process. [8][9][10][11][12] The high level of PCT, on the other hand, has been linked to the effect of cytokines released due to the microvascular interaction during HD.…”
Section: Discussionmentioning
confidence: 99%
“…Cystatin C (CysC) is a small molecular weight protein (molecular weight of 13.3 k Dalton, positively charged with isoelectric point of 9.3) . This protein is produced at a very constant rate and is affected by only a few conditions, such as uncontrolled hyperthyroidism and inflammation . Studies have shown that CysC may be a better surrogate marker for estimating kidney function than creatinine .…”
Section: Introductionmentioning
confidence: 99%
“…3 This protein is produced at a very constant rate and is affected by only a few conditions, such as uncontrolled hyperthyroidism and inflammation. 4,5 Studies have shown that CysC may be a better surrogate marker for estimating kidney function than creatinine. 6,7 We have published three pilot studies and found that: (1) CysC is removed by hemodialysis treatment, (2) its serum concentration is influenced by the weekly dialysis dose (Std Kt/V urea ) but not the per-treatment Kt/V urea , and (3) its serum concentration is stable between dialysis sessions once patients are on an established dialysis prescription.…”
Section: Introductionmentioning
confidence: 99%